TINGKAT PENGETAHUAN KELUARGA DALAM MERAWAT PASIEN STROKE RUANG MERAK II DI RUMAH RSUD ARIFIN ACHMAD PEKANBARU - Muhammad Kailani Yunus; Andalia Roza; Sri Intan Wahyuni (LPPM Universitas Abdurrab, 2016)
Stroke is a disease of functional brain disorders such as nerve paralysis (neurologic deficit) due to impaired blood flow minds around. Knowledge keuarga very influential and important role in the healing process of stroke patients. The purpose of this study to determine how the level of knowledge of the family in caring for stroke patients at the space Merak II hospitals Arifin Achmad Pekanbaru 2013. This research is quantitative, descriptive design. The population in this study were all relatives of patients who had a stroke who were treated at the Peacock Room II hospitals Arifin Achmad. The samples in this study using accidental sampling technique with a sample of 30 men in this study. Research tool that uses the questionnaire. From the analysis of the data obtained the majority of respondents 30-39 years as many as 15 people (50%), the majority of the level of knowledge of the family in caring for stroke patients at home higher by 7 people (23.33%), while as many as 18 people (60%), much lower 5 people (16.66%). expect to health professionals and to better provide health education especially families of stroke patients who would go home in order to care for stroke patients at home.